Evaluation of Intestinal Epithelial Barrier Function in Inflammatory Bowel Diseases Using Murine Intestinal Organoids - Rallabandi, Harikrishna Reddy (Tissue Eng Regen Med, 2020)
BACKGROUND: Intestinal organoids have evolved as potential molecular tools that could be used to study host-microbiome interactions, nutrient uptake, and drug screening. Gut epithelial barrier functions play a crucial role in health and diseases, especially in autoimmune diseases, such as inflammatory bowel diseases (IBDs), because they disrupt the epithelial mucosa and impair barrier function. METHODS: In this study, we generated an in vitro IBD model based on dextran sodium sulfate (DSS) and intestinal organoids that could potentially be used to assess barrier integrity. Intestinal organoids were long-term cultivated and characterized with several specific markers, and the key functionality of paracellular permeability was determined using FITC-dextran 4 kDa. Intestinal organoids that had been treated with 2 µM DSS for 3 h were developed and the intestinal epithelial barrier function was sequentially evaluated. RESULTS: The results indicated that the paracellular permeability represented epithelial characteristics and their barrier function had declined when they were exposed to FITC-dextran 4 kDa after DSS treatment. In addition, we analyzed the endogenous mRNA expression of pro-inflammatory cytokines and their downstream effector genes. The results demonstrated that the inflammatory cytokines genes significantly increased in inflamed organoids compared to the control, leading to epithelial barrier damage and dysfunction. CONCLUSION: The collective results showed that in vitro 3D organoids mimic in vivo tissue topology and functionality with minor limitations, and hence are helpful for testing disease models. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13770-020-00278-0) contains supplementary material, which is available to authorized users.